Organisational energy efficiency and consumption: attitudes, perceptions and behaviour in the context of energy in a South African university - Mapatagane, Ntsundeni Louis (My University, 2020)
The study explores whether individuals' energy consumption behaviours and attitudes are modified to achieve energy efficiency when different feedback formats about the energy consumption of the buildings they occupy are presented to them. It focuses on designing energy behaviour interventions in the form of energy consumption feedback and comparative feedback to investigate whether the intervention will influence more energy-efficient behaviours. The aims of the study were (a) to establish whether energy consumption feedback influences energy-conserving behaviour and; (b) to assessthe attitudes and behaviours of employees towards an energy-conserving behaviour. The study followed a three-step-process. Step one consisted of the intervention of providing energy consumption feedback. Three buildings, used predominantly for office space, teaching and learning, and research and one students' residence located on the university campuses, were selected for the intervention using purposive sampling. In step two of the process a survey was distributed to the building occupants, the survey covered questions on attitudes and behaviour in the workplace coinciding with the components of the theory of planned behaviour (TPB). The last step consisted of the analysis of energy consumption of pre-and post-intervention, including historical data dating back at least three years. The data were analysed using factor analysis and ANOVA. The results of the study provided further evidence that TPB can be used to determine the attitudes and behaviours of employees in the work environment. In line with this theory, Attitudes, Subjective Norm, Descriptive Norm, PBC, Collective outcome expectancy, Injunctive Norm were strong determinants of energy-conserving behaviour. Secondly, the study highlighted that Descriptive Norm and Situational Factors are areas that require particular focus in developing interventions differing from previous studies that suggested PBC, Behavioural Intention and Attitudes as strong determinates of behavioural change. These results further emphasised the need for tailor-made interventions in tackling energy-wasting behaviours. Thirdly, the analyses of the energy consumption data pre and post-intervention, showed a sharp decline in energy consumption, suggesting that the provision of consumption feedback can leave a lasting positive impact in an organisation. Lastly, the results of the regression analysis in this study indicated that the subjective norm, which refers to the perceived social pressure to perform or not to perform the behaviour was the most critical factor for behavioural change